Minimising noise disturbance during ground shooting of pest animals through the use of a muzzle blast suppressor/silencer. (May 2018) - Williams, Warwick; McSorley, Adam; Hunt, Rob; Eccles, Grant
Summary: Lethal control of vertebrate animals through the use of firearms is a component of land management in Australia. The reduction in muzzle blast noise in the area surrounding the shooter provides the opportunity to decrease disturbance of nontargeted animals and nearby humans. This study identifies the reduction in environmental noise footprint provided by suppressor use. This suggests that the use of a suppressor to reduce noise from the muzzle blast may increase operational effectiveness of ground shooting while minimising adverse environmental effects.